Cooperative Principle Maxims Mechanisms in Samsung Indonesia Instagram Reels"™ Captions - Pratama, Hendi; Setiani, Imas; Amalia, Widya; Putri, Stephanie Priyanto (Journal of English Education Program, 2025)
This study explores the application of cooperative principles and illocutionary force in Samsung Indonesia"™s Instagram Reels captions from August 2024. The study aims to evaluate how Grice"™s maxims"”quality, quantity, relevance, and manner"”are employed in captions and how these principles trigger illocutionary acts, particularly calls to action (CTAs). A qualitative approach was used to analyze the linguistic and pragmatic strategies of the captions, focusing on their effectiveness in engaging audiences and influencing behavior. The analysis reveals a strong adherence to the maxims of relevance and quantity, with captions effectively aligning with Reel content and providing sufficient actionable information. However, occasional lapses in the maxims of quality and manner indicate areas for improvement, such as reducing promotional ambiguity and simplifying overly complex phrasing. These improvements could enhance the captions"™ clarity and factual precision. Illocutionary force analysis highlights a predominant use of directive acts, with CTAs designed to prompt specific audience actions, such as exploring products or participating in events. Expressive acts, aimed at evoking emotional responses, were present but less frequently, reflecting a focus on action-oriented engagement. Commissive and assertive acts were minimally observed, indicating a preference for short-term engagement strategies over trust-building. This study concludes that Samsung Indonesia effectively integrates pragmatic principles with strategic CTAs to drive audience interaction and brand engagement. These findings provide valuable insights into optimizing linguistic strategies for social media marketing and contribute to the broader understanding of digital communication practices.